A knowledge management methodology to enhance knowledge transfer between concomitant projects under construction - Lekhema, Lerato (My University, 2019)
The aim of this research work is to develop a knowledge management methodology that will enhance knowledge transfer between concomitant projects under construction in the North West Operating Unit (NWOU), a Distribution division of South Africa’s power utility, Eskom Holdings SOC Ltd. A qualitative study was done to determine the current status of knowledge management in the NWOU. The Construction Activity Based Knowledge Management (ConABKM) framework was applied as a benchmark to assess the state of knowledge transfer in the NWOU. The data indicated a lack of knowledge management implementation in the NWOU’s construction projects; this ranges from utilisation of knowledge management techniques and technologies, implementation of knowledge management processes/activities and management failure. A knowledge management methodology for NWOU was then developed to address these challenges and enhance knowledge transfer between concomitant projects under construction
A research report is submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Engineering. October 2019